Advances of radiation sterilisation in tissue banking - Yusof, Norimah (Springer, 2018)
Under the auspices of the IAEA tissue banking programme on “Radiation Sterilisation of Tissue Graft” conducted from 1985 to 2004, many scientists and surgeons were involved in various regional research and development (R&D) projects mainly in dealing with radiation dose selection, radiation effects on human tissues and quality system in radiation sterilisation. New findings on radiation effects, tissue processing and preservation were shared during the regional and interregional meetings and workshops. Many tissue banks started to use radiation (25 kGy) to sterilize tissue grafts for tissue safety and efficacy and still continue to use it. The IAEA Code of Practice for Radiation Sterilization of Tissues Allografts developed in 2007 offered simpler methods to conduct radiation dose setting and dose validation experiments for tissue grafts. Advances in dose selection and dose mapping are continued under the quality management system when banks need to be certified to continue their operation. The combination of good tissue processing and preservation as well as good radiation practice will ensure the tissue products are properly sterilised thus safe and of high quality. Experience in meeting challenges in using radiation sterilisation and achievements reported by the tissue bankers are shared here.